Dear October : Poems - Morris, Mary, 1953- (Book collections on Project MUSE., 2020)
"The poems of Dear October chronicle the evolution between the natural world and a daughter caring for her mother during the last year of her life. The spirit of home, family, and mother-daughter relationship intertwine with the diversity of culture and ecology in northern New Mexico"--